Perancangan Buku Esai Fotografi Penambang Belerang Kawah Ijen Untuk Menggambarkan Mata Pencaharian Masyarakat Desa Paltuding Banyuwangi - Pratama, Reza Nanda; Bahruddin, Muh; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
Miners Sulfur is a very hard job even their health is at stake to have the purse - purse rupiah. Sulfur miners life is inversely proportional to the abundance of natural resources which should make life more prosperous miners. Wages are not appropriate to make the miners live in poverty, as the backbone of the family who is obliged to make a living, can cause health problems and even death. It was all a picture of life sulfur miners. The lack of public concern to the mining of sulfur makes the sulfur miners living with difficulty and hard work. Therefore, this study aims to create a book of essays photography Sulfur Miners To Illustrating Rural Community Livelihoods Paltuding. Creation of this photography book essay using qualitative data collection methods, namely by interview, observation, documentation studies, literature studies, study competitors are very important to determine the design concept of the study. From the analysis of these data, the theme of the design concept obtained is wise Kata Kunci: Photography Essay Book, Miners Sulfur, Ijen Crater